2022
DOI: 10.3389/fneur.2022.813266
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Dementia in Patients With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis of Population-Based Studies

Abstract: BackgroundMounting evidence suggests that there may be a causal relationship or common pathogenic pathway between inflammatory bowel disease (IBD) and dementia. However, inconsistent results have emerged from epidemiological studies. We therefore conducted this review to clarify the relationship between IBD and dementia.MethodsWe systematically searched PubMed, Web of Science, Embase, and Cochrane library to identify all studies exploring the relationship between IBD and dementia published as of September 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…The present findings mirror the results of a systematic review by Liu et al 5 which concluded that a diagnosis of IBD confers an increased risk of dementia (HR = 1.27, 95% CI 1.10-1.47).…”
Section: Editorial: Ibd and The Risk Of Dementia -The Jury Is Still Outsupporting
confidence: 90%
See 1 more Smart Citation
“…The present findings mirror the results of a systematic review by Liu et al 5 which concluded that a diagnosis of IBD confers an increased risk of dementia (HR = 1.27, 95% CI 1.10-1.47).…”
Section: Editorial: Ibd and The Risk Of Dementia -The Jury Is Still Outsupporting
confidence: 90%
“…The present findings mirror the results of a systematic review by Liu et al 5 which concluded that a diagnosis of IBD confers an increased risk of dementia (HR = 1.27, 95% CI 1.10–1.47). Nevertheless, this systematic review did not include results from the United Kingdom cohort 6 where there was no significant association reported between IBD and dementia.…”
supporting
confidence: 90%
“…However, this study was not stratified by study type, possibly overstating the validity of the results. Another meta-analysis pooling 6 primary studies showed a significantly increased risk of dementia after an IBD diagnosis, regardless of age, gender, dementia subtype, or IBD subtype ( Liu et al, 2022 ). However, the authors did not account for all-cause dementia and AD dementia when pooling effect estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathology of dementia is heterogeneous, understanding the roles of IBD and related medications with specific diseases causing dementia, particularly AD, is more significant to future basic research and precision prevention strategy. After summarizing results from a limited number of studies, recent meta-analyses found a higher risk of AD for IBD patients compared with general healthy population, suggesting a potential pathological detrimental effect of IBD on the development of AD (Liu et al, 2022 ; Szandruk-Bender et al, 2022 ; Zhang et al, 2022 ; Zuin et al, 2022 ). Of note, these reviews did not cover several large-scale population-based studies, which reported extensively inconsistent results (Jussila et al, 2014 ; Sutton et al, 2019 ; Aggarwal et al, 2022 ; Ronnow Sand et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IBD therapies, such as immunosuppressants and TNF-α blockers, may play an important role in the AD development by controlling the inflammation severity (Sutton et al, 2019 ; Aggarwal et al, 2022 ; Ronnow Sand et al, 2022 ). However, the association between medications for managing IBD and risk of AD was not evaluated in previous meta-analyses (Fu et al, 2020 ; Liu et al, 2022 ; Szandruk-Bender et al, 2022 ; Zhang et al, 2022 ; Zuin et al, 2022 ). Thus, we performed an updated systematic review and meta-analysis by summarizing the published data to evaluate the associations of IBD and related medication exposure with risk of AD.…”
Section: Introductionmentioning
confidence: 99%